Human Muscle Precursor Cells Form Human-Derived Myofibers in Skeletal Muscles of Nonhuman Primates: A Potential New Preclinical Setting to Test Myogenic Cells of Human Origin for Cell Therapy of Myopathies. Issue 12 (26th November 2020) - Skuk, Daniel; Tremblay, Jacques P
Abstract: This study aimed to verify if human myogenic cells could participate in muscle regeneration in macaques. This experimental setting would grant researchers a model that could better evaluate the effects of cell therapies in myopathies with a better translation to human patients. Human muscle precursor cells (MPCs) were cultured in vitro and transduced with ß-galactosidase. The cells were subsequently injected into 1-cm 3 muscle regions of 6 macaques immunosuppressed with tacrolimus and dexamethasone. Allogeneic ß-galactosidase+ MPCs were injected in other regions as positive controls. Some cell-grafted regions were electroporated to induce extensive muscle regeneration. MPC-grafted regions were sampled 1 month later and analyzed by histology. There were ß-galactosidase+ myofibers in both the regions grafted with human and macaque MPCs. Electroporation increased the engraftment of human MPCs in the same way as in macaque allografts. The histological analysis (hematoxylin and eosin, CD8, and CD4 immunodetection) demonstrated an absence of cellular rejection in most MPC-grafted regions, as well as minimal lymphocytic infiltration in the regions transplanted with human MPCs in the individual with the lowest tacrolimus levels. Circulating de novo anti-donor antibodies were not detected. In conclusion, we report the successful engraftment of human myogenic cells in macaques, which was possible using tacrolimus-based immunosuppression.